1973
DOI: 10.1073/pnas.70.2.591
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene in Plant Growth

Abstract: Ethylene inhibits cell division, DNA synthesis, and growth in the meristems of roots, shoots, and axillary buds, without influencing RNA synthesis. Apical dominance often is broken when ethylene is removed, apparently because the gas inhibits polar auxin transport irreversibly, thereby reducing the shoot's auxin content just as if the apex had been removed. A similar mechanism may underly ethylene-induced release from dormancy of buds, tubers, root initials, and seeds. Often ethylene inhibits cell expansion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
3

Year Published

1981
1981
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(103 citation statements)
references
References 49 publications
6
94
0
3
Order By: Relevance
“…In all these cases, polyamine biosynthesis was enhanced by growth promoters (6,13,18,21), and suppressed by growth inhibitors (28). Ethylene has been known to suppress growth in etiolated pea seedlings and numerous other plants (1,9). The hormone has been shown to exert this effect by inhibiting cell division in the meristems of the root and shoot apecies (1) and slowing down cell expansion in the subapical regions of these tissues (1).…”
Section: Resultsmentioning
confidence: 99%
“…In all these cases, polyamine biosynthesis was enhanced by growth promoters (6,13,18,21), and suppressed by growth inhibitors (28). Ethylene has been known to suppress growth in etiolated pea seedlings and numerous other plants (1,9). The hormone has been shown to exert this effect by inhibiting cell division in the meristems of the root and shoot apecies (1) and slowing down cell expansion in the subapical regions of these tissues (1).…”
Section: Resultsmentioning
confidence: 99%
“…The increased acid-induced transverse extension is correlated with the deposition of randomly oriented cellulose microfibrils on the inner quarter of the wall (24,25). (2,12,17). Warner and Leopold (30) were able to detect an inhibition of elongation in decapitated seedlings in as little as 6 min.…”
Section: Discussionmentioning
confidence: 99%
“…Such kinetics can hardly be caused by reoriented cellulose microfibrils, even though it is not clear whether the kinetics of lateral expansion exactly parallel the inhibition of elongation. Burg (2) has reported that ethylene can prevent gravitropic curvature of excised pea internode segments within 15 min, probably due to an inhibition of auxin transport. Ethylene did not alter the rate of cell expansion during this time.…”
Section: Discussionmentioning
confidence: 99%
“…If ethylene is removed during the period of intermediate inhibition, the tissue continues to respond at this level (16). The effects of ethylene on elongation are irreversible after a 4-h treatment (16 (2,21,24), but the inhibition of excised segments has been largely overlooked (4). In intact seedlings, the dramatic inhibition of total cell expansion during the first 24 h is probably related to changes in the matrix components and not the newly deposited longitudinal cellulose microfibrils.…”
Section: Kinetics Of Ethylene-induced Lateral Expansionmentioning
confidence: 99%
“…Ethylene inhibits elongation and induces lateral expansion of etiolated pea internode tissue (2,3). Ethylene is thought to affect the mode of growth by altering microtubule and cellulose microfibril orientation (1,9,12,21,26).…”
mentioning
confidence: 99%